2015
DOI: 10.1186/s12913-015-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department and inpatient health care utilization among patients who require interpreter services

Abstract: BackgroundLimited English proficiency is associated with health disparities and suboptimal health outcomes. Although Limited English proficiency is a barrier to effective health care, its association with inpatient health care utilization is unclear. The aim of this study was to examine the association between patients with limited English proficiency, and emergency department visits and hospital admissions.MethodsWe compared emergency department visits and hospitalizations in 2012 between patients requiring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 50 publications
2
45
0
Order By: Relevance
“…Furthermore, socioeconomic differences may impact parental knowledge or comfort level with outpatient management, thus contributing to increased use of the ED among children with cancer. Studies to explore whether language barriers contribute to increased use of the ED is a specific area for further investigation, as language barriers can add a layer of complexity to phone triaging that may be performed by the oncology team prior to referral to the ED …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, socioeconomic differences may impact parental knowledge or comfort level with outpatient management, thus contributing to increased use of the ED among children with cancer. Studies to explore whether language barriers contribute to increased use of the ED is a specific area for further investigation, as language barriers can add a layer of complexity to phone triaging that may be performed by the oncology team prior to referral to the ED …”
Section: Discussionmentioning
confidence: 99%
“…The definition of a frequent ED utilizer has varied substantially in the literature, but has commonly been defined as at least four visits within a 1 year time frame. [9,[16][17][18][19][20][21][22] In this study, we chose a frequent utilization cutoff based on the distribution of the number of ED visits among children with cancer, which happened to align with at least four visits in the year. We revealed that frequent ED utilizers among children with cancer (the top 10th percentile) contributed more than half of ED visits.…”
Section: Factorsmentioning
confidence: 99%
“…Finding the best quality of communication using an interpreter is important to reduce miscommunication since language barriers are central risk factors in relation to healthcare for migrants (Hampers et al 1999;Bischoff 2003;Ramirez et al 2008;Bauer & Alegria 2010;Seffo et al 2014;Ventriglio et al 2014;Njeru et al 2015). Good quality of communication is very central to the health of migrated people (Leininger & McFarland 2006), since migration and integration can lead to positive or negative consequences for the health of the individual (Albin et al 2005;Wallace & Kulu 2014;Syse et al 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Earlier studies in somatic emergency healthcare have shown how language barriers increase risk of misdiagnosis (Hampers et al 1999), lead to limited access to diagnoses, diagnostic testing and treatment (Ramirez et al 2008;Ventriglio et al 2014;) as well as longer stay for the patients at the emergency department (Mahmoud et al 2013;Njeru et al 2015). In psychiatric emergency healthcare, Bauer and Alegria (2010) found that errors by untrained interpreters affected healthcare professionals' ability to understand patients' disordered thoughts or delusional content.…”
Section: Language Barriers and Interpreting Practices In Healthcarementioning
confidence: 99%
“…Patients with LEP who require interpreter services have significantly more ED visits and hospitalizations than patients who do not require interpreter services. [28][29][30] Despite the requirements of the National Standards for Culturally and Linguistically Appropriate Services in Health and Health Care, originally promulgated in 2000 and most recently updated in 2015, 33,34 appropriate interpreter services may not always be immediately available in the ED. Patients with LEP pose special challenges to the use of shared decision making.…”
Section: Limited English Proficiencymentioning
confidence: 99%